Application of bentonite-chitosan nanocomposites for the adsorptive removal of iron and natural organic matter in peat water - Permana, Edwin; Naswir, M.; Wijaya, Dhian Eka; Hidayat, Ali Nurdin; Nurjamil, Dimas Setya; Prayogi, Andrian Setyarestu (Brawijaya University, 2025)
Peat water, commonly found in peatland regions, often poses a challenge as a water source due to its high content of iron and natural organic matter (NOM). This research investigated the development and application of bentonite–chitosan nanocomposites as an effective adsorbent for reducing iron metal and NOM concentrations in peat water. Chitosan was synthesized from tilapia fish scales through demineralization, deproteinization, and deacetylation processes, then characterized for moisture content (7.4%), ash content (5.4%), and functional groups using FTIR spectroscopy. Bentonite was thermally and chemically activated with sulfuric acid to increase its adsorption capacity. Nanocomposites were prepared with varied bentonite-to-chitosan ratios (90:10, 70:30, 50:50) using sodium tripolyphosphate (STPP) as a crosslinker. FTIR and XRD analyses confirmed the formation of nanocomposites and revealed structural changes post-adsorption, including reduced crystallinity and increased particle size. Adsorption studies showed that the 90%Bt-10%Ch3 formulation achieved the highest iron removal efficiency (68.6%) with an adsorption capacity of 0.084 mg/g. Meanwhile, the 50%Bt-50%Ch3 formulation demonstrated the highest NOM removal efficiency (36.8%) with a capacity of 36.80 mg/g. The results indicate that bentonite is more effective for iron adsorption, while chitosan plays a key role in removing NOM due to its amine and hydroxyl functional groups. This study highlights the potential of utilizing fishery waste and natural minerals to produce low-cost, eco-friendly nanocomposites for improving water quality in peatland environments.